Prognostic value of the Fas/Fas-ligand system in breast cancer - Bębenek, Marek; Duś, Danuta; Koźlak, Joanna (Contemporary Oncology/Współczesna Onkologia, 2013)
Fas and its ligand (FasL) are known to play a crucial role in the genetically controlled mechanism of cell death, and their deregulation in cancer cells is involved in the immune escape of the tumor. The aim of this review is to analyze the current knowledge on the prognostic value of Fas/FasL in breast cancer patients. Both the results of other authors and our own experiences indicate that the lack of Fas ligand, and particularly Fas, is related to a significantly worse prognosis. It probably results from the resistance of Fas-deficient breast tumors to the mechanisms of apoptosis. On the other hand, some results suggest that the Fas/FasL-dependent mechanisms of tumor spread may be different for various target tissues. The expression of the Fas/Fas-ligand system has potential prognostic application in view of current knowledge, and consequently should be considered as an additional prognostic factor in breast cancer patients.